Unpacking the Cycle of Recidivism: A Study of Age, Crime, and Contributing Factors - Akram, Areej; Irfan, Saira; Aziz, Ayesha (Applied Psychology Review, 2025)
Recidivism has been a challenge in the criminal justice systems globally, as individuals continue to reoffend even after previous interventions. The current qualitative research explores the nature of the factors that underlie recidivism, with an emphasis on demographic features, including age and type of crimes. Based on a phenomenological approach, the study involved 20 inmates (15 men and 5 women) from Central Jail Sahiwal, selected through purposive sampling. Colaizzi’s method was used to analyze the data, which identified three key themes, namely economic factors, psychological factors, and social factors. These key themes further gave way to subthemes, such as poverty, inflation, feelings of inferiority, lack of self-control, family and peer influence, revenge, and unwarranted accusations against offenders. The findings revealed that younger adults were more likely to engage in robbery and drug-related offences mainly due to economic instability, lack of personal control, and social inferiority. Contrarily, middle-aged and older offenders were involved in violent crimes influenced by social influence or revenge motives. The most frequent types of offence committed by the offenders were drug-related followed by robbery and murder. In conclusion, the current research highlights the complexity of reoffending behavior and the importance of a custom approach that would consider individual factors and holistic structural inequalities.